Nasal High-Flow Therapy in Infants and Children - Donna Franklin; Andreas Schibler (Pediatric Respirology and Critical Care Medicine)
This review highlights and summarizes the current evidence and knowledge of nasal high flow therapy management in infants and children. This review outlines the distinct differences in the use of NHF therapy between children and adults. A comprehensive literature review has been performed reviewing the relevant physiological studies and current evidence of support measures in these children. Despite the quick uptake of nasal high flow therapy in the clinical area there has been limited high-grade evidence, with new studies showing beneficial results with the use of nasal high flow therapy in acute respiratory disease and children.